RANCANG BANGUN BANDPASS FILTER MIKROSTRIP METODE HAIRPIN PADA FREKUENSI 2.3 GHZ - Orifansyah, Afif (JURNAL PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA (JVoTE), 2020)
Abstract. This study aims to design and test the microstrip bandpass filter with the hairpin method at a frequency (2.3 GHz to 2.4 GHz), with a bandwidth of 100MHz. The research was carried out at the 4th Floor Telecommunication Laboratory (L1 Building) of the State University of Jakarta, in March - October 2016. The hairpin method microstrip bandpass is the development of an edge coupled bandpass microstrip, the Haipin filter concept has a resonator length λ / 2 which is coupled in parallel and the shape of the resonator is like the letter 'U'. This technique is the development of parallel couple where the λ / 4 couple line channel is folded by L or ((λ / 4) -b), b is the length of the channel that is not coupled. From the research results the hairpin band pass filter is made and tested in a simulation with the results calculations are then simulated using the fabrication and measurement results. So it can be concluded that the hairpin bandpass filter was successfully designed in CST Microwave Studio software, fabricated, and tested using a network analyzer measuring instrument with a cut-off frequency parameter of 2.355 GHz and a bandwidth of 106 MHz.